1980
DOI: 10.1126/science.210.4470.650
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 Nuclear Magnetic Resonance Study of Osmoregulation in a Blue-Green Alga

Abstract: The process of osmoregulation in a unicellular blue-green alga, Synechococcus sp., has been studied by natural-abundance carbon-13 nuclear magnetic resonance spectroscopy of intact cells and cell extracts. 2-O-alpha-D-Glucopyranosylglycerol was identified as the major organic osmoregulatory solute. This demonstrates the presence of a major osmoregulatory solute in a blue-green alga and is also an example of an osmoregulatory role for glucosylglycerol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 10 publications
3
55
0
Order By: Relevance
“…In cyanobacteria, a close correlation has been shown between major accumulated compatible solutes and the range of salt tolerance (Blumwald et al, 1983;Borowitzka et al, 1980;Mackay et al, 1984;Reed et al, 1984). Cyanobacteria are classified into three groups of salt tolerance depending on the types of osmoprotective compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In cyanobacteria, a close correlation has been shown between major accumulated compatible solutes and the range of salt tolerance (Blumwald et al, 1983;Borowitzka et al, 1980;Mackay et al, 1984;Reed et al, 1984). Cyanobacteria are classified into three groups of salt tolerance depending on the types of osmoprotective compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of osmoregulation may vary in different species. For marine cyanobacteria, the accumulation of glucopyranosylglycerol in Synechococcus sp Nageli (4), and K+ ions in Aphanotheca halophytica (14) sucrose occurs in Nostoc muscorum (1), and in Synechococcus 6311 (3). Glucopyranosylglycerol accumulation occurs in Synechocystis 6308 (12).…”
Section: Abstracimentioning
confidence: 99%
“…Studies have been carried out on the marine mollusc Tapes watlingi (Norton, 1979;Norton & de Rome, 1980), in which taurine, betaine and glycine play a role in osmoregulation. The technique has also been used by Borowitzka et al (1980) to study a cyanobacterium, Synechococcus sp., which was found to use glucosylglycerol as the major osmoregulatory solute. It has since been shown that glucosylglycerol is accumulated by all species of marine cyanobacteria in response to osmotic stress (Mackay et af., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…A number of species in the genus DunaZieIIa have been shown to use glycerol as the primary osmoregulatory solute (Craigie & McLachlan, 1964;Ben-Amotz & Avron, 1973;Borowitzka & Brown, 1974). Compounds which have been identified as osmoregulators in other species of algae include floridoside (Kauss, 1969), isofloridoside (Kauss, 1967), cyclohexanetetrol (Craigie, 1969), mannitol (Hellebust, 1976), mannisido-mannitol (Feige, 1972), sucrose (Wetherell, 1963), sorbitol and proline (Brown & Hellebust, 1978) and glucosylglycerol (Borowitzka et al, 1980;Mackay et al, 1983). The xerophilic yeast, Saccharomyces rouxii has been shown to accumulate glycerol efficiently in response to low external a, (Brown, 1978), but the highly salt-tolerant yeast Debaryomyces hansenii accumulates K + intracellularly, as well as glycerol, as the salinity of the culture medium increases (Gustafsson & Norkrans, 1976).…”
Section: Introductionmentioning
confidence: 99%